Animal Foetal Models of Obesity and Diabetes – From Laboratory to Clinical Settings - Grzęda, Emilia; Matuszewska, Julia; Ziarniak, Kamil; Gertig-Kolasa, Anna; Krzyśko- Pieczka, Izabela; Skowrońska, Bogda; Sliwowska, Joanna H. (Frontiers in Endocrinology, 2022)
The prenatal period, during which a fully formed newborn capable of surviving outside its mother’s body is built from a single cell, is critical for human development. It is also the time when the foetus is particularly vulnerable to environmental factors, which may modulate the course of its development. Both epidemiological and animal studies have shown that foetal programming of physiological systems may alter the growth and function of organs and lead to pathology in adulthood. Nutrition is a particularly important environmental factor for the pregnant mother as it affects the condition of offspring. Numerous studies have shown that an unbalanced maternal metabolic status (under- or overnutrition) may cause long-lasting physiological and behavioural alterations, resulting in metabolic disorders, such as obesity and type 2 diabetes (T2DM). Various diets are used in laboratory settings in order to induce maternal obesity and metabolic disorders, and to alter the offspring development. The most popular models are: high-fat, high-sugar, high-fat-high-sugar, and cafeteria diets. Maternal undernutrition models are also used, which results in metabolic problems in offspring. Similarly to animal data, human studies have shown the influence of mothers’ diets on the development of children. There is a strong link between the maternal diet and the birth weight, metabolic state, changes in the cardiovascular and central nervous system of the offspring. The mechanisms linking impaired foetal development and adult diseases remain under discussion. Epigenetic mechanisms are believed to play a major role in prenatal programming. Additionally, sexually dimorphic effects on offspring are observed. Therefore, further research on both sexes is necessary.